2016
DOI: 10.1038/srep31545
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of microglia improves cognitive function following cranial irradiation

Abstract: Cranial irradiation for the treatment of brain cancer elicits progressive and severe cognitive dysfunction that is associated with significant neuropathology. Radiation injury in the CNS has been linked to persistent microglial activation, and we find upregulation of pro-inflammatory genes even 6 weeks after irradiation. We hypothesize that depletion of microglia in the irradiated brain would have a neuroprotective effect. Adult mice received acute head only irradiation (9 Gy) and were administered a dietary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
221
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(236 citation statements)
references
References 37 publications
15
221
0
Order By: Relevance
“…Eye drops of MC were administered once or twice a day from 3 days before to 7 days after NMDA injection ( Figure 3a). PLX3379 (Elmore et al, 2014) and PLX significantly reduce microglial number in the brain (Acharya et al, 2016). PLX3379 (Elmore et al, 2014) and PLX significantly reduce microglial number in the brain (Acharya et al, 2016).…”
Section: Instillation Of MCmentioning
confidence: 94%
“…Eye drops of MC were administered once or twice a day from 3 days before to 7 days after NMDA injection ( Figure 3a). PLX3379 (Elmore et al, 2014) and PLX significantly reduce microglial number in the brain (Acharya et al, 2016). PLX3379 (Elmore et al, 2014) and PLX significantly reduce microglial number in the brain (Acharya et al, 2016).…”
Section: Instillation Of MCmentioning
confidence: 94%
“…In one of our previous studies, we have indicated that cranial irradiation can cause transient accumulation of microglial cells followed by persistent inflammation and pronounced expression of IL‐1β and CCL2 in the hippocampus (Han et al, ). Indeed, neuroinflammation induced by activated resident microglia as well as infiltrating monocytes plays a pivotal role in hippocampal‐dependent severe cognitive dysfunction after both acute and long‐term irradiation (Feng et al, ) and microglial depletion can ameliorate these cranial radiation‐induced cognitive deficits (Acharya et al, ). Confirmed in another study, PLX5662‐mediated depletion can lead to protection from loss of dendritic spines, reduction of CD11b + Ly6G − Ly6C hi monocytes in the blood, inhibition of monocyte accumulation and ultimately prevention of radiation‐induced cognitive abnormalities (Feng et al, ).…”
Section: Depleting Microglia In Diseases: the Friend In Need May Not mentioning
confidence: 99%
“…Recently, a new compound, PLX5622, which acts as specific dietary inhibitor of colony stimulating factor-1 receptor (CSF1R), a tyrosine kinase transmembrane receptor essential for the survival and activation of monocytes and macrophages in the periphery and microglia in the CNS (Erblich et al, 2011;Hamilton and Achuthan, 2013;Elmore et al, 2014), was shown to efficiently eliminate microglia in mice (Dagher et al, 2015). Similar to the less specific CSF1R inhibitor PLX3397 , PLX5622 has been used to study the role of microglia in several conditions of brain injury (Acharya et al, 2016;Feng reported that microglia depletion by PLX5622 increases virus replication and subsequent mortality in response to intracerebral infection with mouse hepatitis virus (MHV; Wheeler et al, 2018) or flaviviruses (West Nile virus and Japanese encephalitis virus; Seitz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%